2005
DOI: 10.1149/1.1851056
|View full text |Cite
|
Sign up to set email alerts
|

Wet-Chemical Treatment of Si[sub 3]N[sub 4] Surfaces Studied Using Infrared Attenuated Total Reflection Spectroscopy

Abstract: Infrared attenuated total reflection spectroscopy has been used to observe the surface chemistry of Si 3 N 4 films ͑grown on Si by low-pressure chemical vapor deposition͒ under steady-state conditions during exposure to dilute aqueous HF solutions. Surfaces etched in HF do not exhibit rapid growth of an SiO 2 layer when subsequently exposed to either humid room air at room temperature or to liquid H 2 O. However, some evidence is found for the formation of an ultrathin oxide-like layer when the etched surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 65 publications
(110 reference statements)
2
23
0
Order By: Relevance
“…To test this idea, concentrated HCl was introduced into the pore to decrease the pH to 1 ([H + ] = 100 mM). HCl was chosen because it supposedly does not etch silicon nitride with a low oxide content 43 . Unlike the current measured in electrolyte at pH 6 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To test this idea, concentrated HCl was introduced into the pore to decrease the pH to 1 ([H + ] = 100 mM). HCl was chosen because it supposedly does not etch silicon nitride with a low oxide content 43 . Unlike the current measured in electrolyte at pH 6 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We note that, in contrast to our observations, previous studies have reported that 1-octadecene can chemisorb onto SiO 2 and Si 3 N 4 surfaces, [14,15] However, a subsequent spectroscopic study showed that those results might be due to the existence of SiH x sites after surface treatment, leaving the surface with reactive groups like those present on bare silicon instead of only SiO 2 or Si 3 N 4 . [16] In our study, we used piranha treatment before HF etching and this hydroxylated the hydrophilic dielectric surface. Consequently, less SiH x may exist on the SiO 2 (or Si 3 N 4 or HfO 2 ) surfaces after this treatment.…”
mentioning
confidence: 99%
“…Tailoring the pH buffering effect is considered to be key in boosting up cell metabolism without damaging the cells, as ammonia elution beyond a given (unknown so far and different for different types of cells) concentration threshold could be hard for the cells to metabolize. An alternative route to control elution was tried by tuning only the outer surface chemistry: the A-Si 3 N 4 sample was treated with acetic acid because there are proofs that treatments in concentrated acetic acid can be used to remove (by esterification) the Si-OH silanol groups that form on the surface of Si 3 N 4 [ 38 ]. The silanol groups are then restored in aqueous environments, making the surface of the A-Si 3 N 4 powders more reactive in the initial stages of hydrolysis; The T-Si 3 N 4 sample was obtained by treating the powder at a relatively low temperature (200 °C) in order to produce a thin SiO 2 layer on the outer surface, with the ultimate goal of reducing the reactivity of the powder surface [ 39 ] without affecting the bulk of the material.…”
Section: Discussionmentioning
confidence: 99%